Tribological response of laser-textured steel pins with low-dimensional micrometric patterns. (September 2020) - Fiaschi, Giulia; Di Lauro, Michele; Ballestrazzi, Antonio; Rota, Alberto; Biscarini, Fabio; Valeri, Sergio
Abstract: Our purpose was to study the tribological effects of surface texturing at the mesoscale, generally disregarded. We realized hemispherical dimples on 100Cr6 steel pins using a ns-pulsed Nd:YAG laser. Both radius and depth of the patterns fall in the very-low part of the micrometric scale, ranging respectively from 10 to 13  μ m and from 4 to 6.5  μ m. To map Stribeck curves, we used a pin-on-disk apparatus and a commercial motor oil as lubricant. The results confirm that the post-texturing lapping process is crucial to achieve a reduction in the coefficient of friction. These patterns show a tribological effect mainly in mixed lubrication regime, and partially in hydrodynamic regime. Even very small differences in radius and depth may induce very different response, evidencing the need of very fine tuning of the geometrical characteristics of the patterns. The lower friction was recorded for larger and deeper dimples. Friction reduction for increasing dimples density has been found as well. Endurance tests in boundary lubrication regime show a more stable coefficient of friction and a larger mean lifetime of patterned surfaces with respect to polished one. Furthermore, water-contact-angle tests show a weak hydrophobic effect for high aspect ratio patterns. However, no correlation was observed between wettability and tribological response. Highlights: Few-microns wide and deep circular dimples realized by laser ablation on steel pins. Textured pins show a lower coefficient of friction in mixed-lubrication regime. A higher dimple density leads to lower coefficient of friction compared to a flat pin. In boundary lubrication regime textured pins show a more stable CoF. No correlation observed between wettability and tribological response of textured pin.